Kegiatan Skrining Indeks Massa Tubuh, Lingkar Pinggang, Dan Lingkar Pinggul Pada Usia Produktif Sebagai Deteksi Dini Obesitas Dan Komplikasi Terkait Obesitas Di Sekolah SMP Kalam Kudus - Ernawati Ernawati; Joshua Kurniawan; Gunaidi, Farell Christian; Fernando Nathaniel; Ranindita Maulya Ismah Amimah; Raden Seliwat Agung Aditya (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Obesity, characterised by excessive or abnormal fat accumulation, poses significant health risks. The prevalence of obesity in Indonesia's adult population increased from 14.8% in 2013 to 21.8% in 2018, with central obesity rising from 26.6% to 31%. Contributing factors include genetics, lifestyle, psychological stress, and socioeconomic status. Although the Body Mass Index (BMI) is a standard measurement for assessing obesity, BMI does not accurately reflect the composition or distribution of body fat. Therefore, additional anthropometric measurements such as waist and hip circumference are essential. This activity uses the PDCA (Plan-Do-Check-Action) methodology to screen for obesity in adults at Kalam Kudus Middle School, West Jakarta. Of the 129 participants, 26 people (20.16%) were overweight and 35 people (27.14%) were obese. Waist circumference indicated central obesity in 61 women (47.29%) and 19 men (14.73%). Hip circumference showed that 9 men and women (6.98%) had a high risk of metabolic disease. Anthropometric measurements provide important insights into obesity and its health implications, emphasising the need for regular screening and lifestyle modification.